What is Philosophy? The Role of Philosophy in Culture - Piórczyński, Józef (Practica et Speculativa: Studies Offered to Professor Andrzej M. Kaniowski, 2022)
Achieving great results, science and its ideological form, scientism, cannot eliminate philosophy from culture. The loss of cognitive, emotive and existential value and actuality puts an end to every philosophy with its method, object, and solutions to its constituent matters. The incompleteness of human existence, which is determined by the search for meaning and truth, is constantly bound to negate of the ever-new attempts to resolve philosophical issues.